2004
DOI: 10.1152/ajpheart.00356.2004
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl cyclase type VI corrects cardiac sarcoplasmic reticulum calcium uptake defects in cardiomyopathy

Abstract: Calcium malfunction plays a central role in heart failure. Here, we provide evidence that adenylyl cyclase type VI restores sarco(endo)plasmic reticulum 2a (SERCA2a) affinity for calcium and maximum velocity of cardiac calcium uptake by sarcoplasmic reticulum in murine dilated cardiomyopathy. Restoration of normal SERCA2a affinity for calcium is associated not only with decreased phospholamban protein expression but also with increased phospholamban phosphorylation by PKA activation. The ratio of phosphorylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 43 publications
1
42
0
Order By: Relevance
“…Both defective calcium uptake by SERCA2a and defective calcium release through the SR calcium release channel ryanodine receptor 2 (RyR2) occur in clinical and animal models of heart failure. 9,15,16 In the present study, we found that AC VI expression was associated with increased SERCA2a affinity for calcium ( Figures 7C and 7D). This improvement of calcium uptake by AC VI was associated with increased phosphorylation of phospholamban at Ser16; protein contents of phospholamban and SERCA2a were unchanged ( Figures 7A and 7B).…”
Section: Discussionsupporting
confidence: 64%
“…Both defective calcium uptake by SERCA2a and defective calcium release through the SR calcium release channel ryanodine receptor 2 (RyR2) occur in clinical and animal models of heart failure. 9,15,16 In the present study, we found that AC VI expression was associated with increased SERCA2a affinity for calcium ( Figures 7C and 7D). This improvement of calcium uptake by AC VI was associated with increased phosphorylation of phospholamban at Ser16; protein contents of phospholamban and SERCA2a were unchanged ( Figures 7A and 7B).…”
Section: Discussionsupporting
confidence: 64%
“…Again, this study is based on extensive preclinical data showing that increasing adenylyl cyclase VI activity would increase cAMP levels and, hence, SERCA activity and contractility in experimental heart failure. 24 …”
Section: Restoration Of Serca As a Therapeutic Strategymentioning
confidence: 99%
“…11,17 Additional experiments to measure cAMP production were also performed with myocardial homogenates from neonatal mice (1 day Activities of intrinsic protein kinase A (PKA) and protein phosphatases 1 (PP1) and 2A (PP2A) were measured as described previously. 11,16 Western blotting was performed as described previously. 16 Additional experiments were conducted with LV samples from isolated hearts perfused with dobutamine (10 mol/L, 5 minutes).…”
Section: ؉mentioning
confidence: 99%
“…11,16 Western blotting was performed as described previously. 16 Additional experiments were conducted with LV samples from isolated hearts perfused with dobutamine (10 mol/L, 5 minutes).…”
Section: ؉mentioning
confidence: 99%